Longterm oral cisapride improves interdigestive antroduodenal motility in dyspeptic patients. Issue 3 (March 1990) - Testoni, P A; Bagnolo, F; Fanti, L; Passaretti, S; Tittobello, A
Abstract : We have evaluated the effect of cisapride on interdigestive antroduodenal motility during a prolonged oral therapy in 20 consecutive dyspeptic subjects. Individuals with less than two migrating motor complexes (MMCs) starting from the antral region in 240 minutes and without evidence of upper gastrointestinal tract diseases were randomly treated with either cisapride (10 cases), or placebo (10 cases) for 15 days. Computerised manometry of antroduodenal region was performed for 240 minutes, in basal conditions and on the 15th day of therapy. Symptomatic evaluation of patients was also performed before and after treatment. After cisapride administration, a significant increase in the incidence of antral migrating motor complexes was noticed (p = 0.022); likewise, the motility index, calculated for phase-2 periods, appeared to be significantly higher both in the antrum and in the duodenum (p less than 0.001). Symptomatic improvement was observed in both groups, with a hardly significant (p = 0.049) reduction of dyspeptic symptoms severity only but not of frequency in cisapride treated patients v controls. We conclude that longterm oral therapy with cisapride improves interdigestive antroduodenal motor activity.